Sistema Tutor Inteligente PAT2Math: Proposta de Arquitetura Multiagente - Damasceno, Fábio R.; Cruz, Anderson da; Jaques, Patrícia A. (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2010)
As the development of an Intelligent Tutor System (ITS) is a quite complex, it should be modularized for its complexity reduction and better problem comprehension. A multi-agent approach has been applied in the conception of ITSs, as it allows to share specific roles in specialised agents. In this way, this article presents the analysis process steps of the ITS PAT2Math architecture, that was built under a multi-agent approach. This architecture was projected following the Prometheus Methodology.